(untitled) (American Journal of Islam and Society, 2006)
Books Reviewed: Jack Weatherford, Genghis Khan and the Making of the Modern World. New York: Crown Publishers, 2004; Thomas T. Allsen, Culture and Conquest in Mongol Eurasia. UK: Cambridge University Press, 2001; Justin Marozzi, Tamerlane: Sword of Islam, Conqueror of the World. London: HarperCollins, 2004. What these books have in common is their attempt to recast our perceptions of the Mongols’ impact upon the Islamic world. Given the lore of gore thrown up by the intervening centuries, the authors clearly had their work cut out for them. Over the course of those centuries, hardly a schoolchild or even an illiterate villager anywhere in the Islamic world, and certainly in Muslim Central Asia, was not taught to dread and despise the very mention of the Mongols – and especially their two most infamous and notorious leaders, Genghis Khan and Tamerlane. To a great degree, the same holds true for children in other parts of the world, especially in Europe, where the works of Chaucer, Marlowe, and others contributed greatly to the vilification of these two Mongols. After reading the three books under review, there is no option for the careful reader but to reassess his/her own understanding of the Mongol centuries (the thirteenth and fourteenth CE) and, indeed, of how history may rightly or wrongly be represented and perceived. Much of the information presented in these books is truly eye-opening. There is probably just as much that is ultimately material for continued scholarly consideration and interpretation. However, it is at the human level that any such reading must begin. If history is really a matter of perspective, let me begin by quoting from Justin Marozzi’s work: Such cultural benefits to Persia of Mongol rule were all very well. But, as David Morgan concluded in a recent study of medieval Persia: “We may justly have our doubts over how impressed the Persian peasants, as they did their best to avoid the Mongol tax-collectors, would have been by developments in miniature painting. For Persia, the Mongol period was a disaster on a grand and unparalled scale.” ...